INTELLIGENT PACKAGING AS A MARKETING TOOL. ARE DIGITAL TECHNOLOGIES RE-SHAPING PACKAGING? - Iza Gigauri; Maria Palazzo (Agora International Journal of Economical Sciences (AIJES), 2023)
Rapid technological advancements, digitalization trends, changes in consumer behavior, and call to achieve sustainable development goals induce transformations in the packaging industry. Digital technologies are enabling the packaging to move from its core passive functions to more enhanced features such as prolonged preservation, traceability, communication, sustainable supply chain, life-cycle evaluation, and extended shelf-life of a product. Intelligent packaging can provide information about the conditions inside and outside of the packaging preventing contamination of the product. Monitoring of food products allows consumers, producers, and retailers to avert potential spoilage and unnecessary waste. Consumer behavior determines the success of intelligent packaging. Their acceptance of new technologies, environmental concerns, attitude towards sustainability issues, as well as safety and quality preferences define customers' buying behavior. The innovative features of packaging have not yet attracted much attention from academics and practitioners. In addition, the design and development of such packaging are associated with high prices, which encourages manufacturers to avoid it. Therefore, a comprehensive understanding of current packaging trends can shed light on the benefits and potential barriers to its use. This paper provides a literature review of intelligent packaging and explains its functions. It defines the role of packaging in marketing in the current digital era. The paper discusses the definitions of smart, active, and intelligent packaging and suggests how intelligent packaging can serve as a marketing tool while achieving marketing strategies.
Keywords: 330